HUBUNGAN TINGKAT STRESS DENGAN INSOMNIA PADA MAHASISWA - Ruswati Ruswati; Marwati Marwati; Yani Trihandayani (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Everyone, including children, adults, and parents, can experience stress. Academic stress is a common type of stress that occurs in a school or educational environment. Students who face high pressure, such as numerous assignments, may experience stress that can lead to insomnia. The purpose of this study is to examine the relationship between stress and insomnia in students. Stress is a negative feeling caused by situations beyond one's control or changes in one's body and mind. Insomnia is the inability to achieve adequate quality and quantity of sleep. A literature review study was conducted, with 5 journals obtained from Google Scholar. The study design was cross-sectional. The results showed a significant relationship between stress and insomnia in college students (p <0.05). This means that stress levels have a moderate positive correlation with insomnia levels. In conclusion, it is important for students to learn how to manage their stress levels to prevent insomnia.